Effectiveness of Balloon Angioplasty and Stent Angioplasty: Wound Healing in Critically Limb Ischemic - Pamungkas, Wisnu; Darwis, Patrianef (The New Ropanasuri Journal of Surgery, 2019)
Introduction. Critical limb ischemia (CLI) is a vascular disease that has a significant amputation and mortality risk with diabetes mellitus; the most significant risk factor in CLI is prevalent among Indonesian. Endovascular intervention (EVI) is preferred in treating CLI because it is non-invasive and effective. Balloon angioplasty and stent angioplasty are the most common method of EVI in Indonesia. This study aims to compare the effectiveness of balloon angioplasty and stent angioplasty on wound healing in CLI. Method. A cross sectional study enrolled 90 subjects of CLI who underwent endovascular intervention using balloon angioplasty dan stent angioplasty from January 2013 to July 2017 in dr. Cipto Mangunkusumo General Hospital, Jakarta. The wound healing period between balloon angioplasty dan stent angioplasty analysed using an unpaired T-test. Results. The wound healing period in balloon angioplasty and stent angioplasty distributed normally. The mean value of the wound healing period in balloon angioplasty and stent angioplasty is 84.8 ± 2.423 and 59.93 ± 2.423 days with a mean difference of 25 days. The difference in the wound healing period in both groups is statically significant. Conclusion. Stent angioplasty is a better method than balloon angioplasty for wound healing in patients with CLI.